2020
DOI: 10.3390/microorganisms8030340
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Microdochium Fungi Associated with Cereal Grains in Russia

Abstract: In total, 46 Microdochium strains from five different geographic regions of Russia were explored with respect to genetic diversity, morphology, and secondary metabolites. Based on the results of PCR, 59% and 28% of the strains were identified as M. nivale and M. majus, respectively. As a result of sequencing four genome regions, namely ITS, LSU, BTUB, and RPB2 (2778 bp), five genetically and phenotypically similar strains from Western Siberia were identified as M. seminicola, which, according to our findings, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 56 publications
0
17
2
4
Order By: Relevance
“…Изучение загрязненности зерна урожаев 2005-2010 годов показало, что в среднем по России степень контаминации ДОН гораздо ниже МДУ (18,19), наиболее загрязнено зерно из Южного и Северо-Кавказского федеральных округов (20). Эти территории наряду с Дальневосточным федеральным округом традиционно считаются ареалами фузариоза зерновых в России (17,21). В то же время вследствие изменения климата и обмена семенным материалом происходит постепенное продвижение более агрессивных патогенов на север: например, F. graminearum -продуцент ДОН и ЗЕА выявляют в зерне, выращенном на северо-западе России (22).…”
unclassified
“…Изучение загрязненности зерна урожаев 2005-2010 годов показало, что в среднем по России степень контаминации ДОН гораздо ниже МДУ (18,19), наиболее загрязнено зерно из Южного и Северо-Кавказского федеральных округов (20). Эти территории наряду с Дальневосточным федеральным округом традиционно считаются ареалами фузариоза зерновых в России (17,21). В то же время вследствие изменения климата и обмена семенным материалом происходит постепенное продвижение более агрессивных патогенов на север: например, F. graminearum -продуцент ДОН и ЗЕА выявляют в зерне, выращенном на северо-западе России (22).…”
unclassified
“…С помощью иммуноферментного анализа (ИФА) и метода высокоэффективной жидкостной хроматографии в сочетании с масс-спектрометрией (ВЭЖХ-МС/МС) анализировали содержание микотоксинов в зерне, а также определяли токсинопродуцирующую способность штаммов F. langsethiae. Детектирование и количественное определение микотоксинов осуществляли по сертифицированным методикам (Кононенко и др., 1999;Гагкаева, Гаврилова, 2013;Gagkaeva et al, 2019Gagkaeva et al, , 2020.…”
Section: материалы и методыunclassified
“…Таблица. Информация о встречаемости F. langsethiae в разных регионах России (Gagkaeva et al, 2020). Анализ контаминации микотоксинами образцов зерна, в которых был выявлен F. langsethiae показал, что в образцах зерна овса, имеющих относительно высокую (7 %, Вологодская область) и максимальную выявленную зараженность (14 %, Московская область), суммарное количество Т-2 и НТ-2 токсинов, выявленное с помощью ИФА, составило 186 и 1230 мкг/кг.…”
Section: результаты и обсуждениеunclassified
“…The quantitative and qualitative composition of the snow mold-causing community greatly varies depending on the crop, region, and ecological conditions (Chang et al 2006 ). In Russia, an analysis of 46 strains from five regions revealed that 59% of the strains were M. nivale and 28.3% were M. majus (Gagkaeva et al 2020 ). Also, in the Central and Northwestern European regions of Russia, M. nivale is predominant and accounts for 64.7% of the analyzed strains from this territory.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, M. seminicola M. Hern.—Restr., Seifert, Clear & B. Dorn was first discovered in Russia (Gagkaeva et al 2020 ). M. seminicola causes symptomless endophytic infections in cereals, and, from an ecological perspective, additional information about the distribution of this species would be essential.…”
Section: Introductionmentioning
confidence: 99%